Prudence wants a pet - Daly, Cathleen; King, Stephen Michael (New York : Roaring Brook Press, 2011)
Prudence is determined to have a pet in spite of her parents' objections, but a branch, a twig, a car tire, and even her baby brother fail to make her dreams come true.
"A Neal Porter Book."
Kirkus Starred
Pub Weekly
School Library Journal
Kirkus Starred, May 2011
Pub Weekly, May 2011
Keywords: Pets -- Juvenile fiction; Pets -- Fiction; Pets -- Fiction; Picture books for children